A user‐assisted thread‐level vulnerability assessment tool. (20th November 2018) - Oz, Isil; Topcuoglu, Haluk Rahmi; Tosun, Oguz
Summary: The system reliability becomes a critical concern in modern architectures with the scale down of circuits. To deal with soft errors, the replication of system resources has been used at both hardware and software levels. Since the redundancy causes performance degradation, it is required to explore partial redundancy techniques that replicate the most vulnerable parts of the code. The redundancy level of user applications depends on user preferences and may be different for the users with different requirements. In this work, we propose a user‐assisted reliability assessment tool based on critical thread analysis for redundancy in parallel architectures. Our analysis evaluates the application threads of a parallel program by considering their criticality in the execution and selects the most critical thread or threads to be replicated. Moreover, we extend our analysis by exploring critical regions of individual threads and execute redundantly only those regions to reduce redundancy overhead. Our experimental evaluation indicates that the replication of the most critical thread improves the system reliability more (up to 10% for blackscholes application) than the replication of any other thread. The partial thread replication based on critical region analysis also reduces the vulnerability of the system by considering a fine‐grained approach.